Persepsi guru tentang program perkembangan staf di sekolah : satu kajian di beberapa buah Sekolah Rendah Daerah Kuching - Maimunah, Bujang (1998)
This study aims to identify teachers' perception towards School-based Staff Development Program (SSDP). The objectives of this study are to identify the level of implementation of SSDP in schools, teachers perception on the importance of SSDP in school and the level of support by the school management towards SSDP. The study also analyze the differences between level of implementation of SSDP and the schools' background characteristics, the differences between levels of support by school management towards SSDP and the schools' background characteristics, to analyze teachers' perception towards the importance of SSDP and respondents' background characteristic, to examine the relationship between the level of management support and the level of the implementation of SSDP in schools and to examine the relationship between level of management support and teachers' perception towards SSDP.